Analysis of the types of Reinholdella, an important Jurassic foraminiferal genus - M. Apthorpe (Journal of Micropalaeontology, 2025)
The important Jurassic foraminiferal genus Reinholdella is described and redefined based on the extant holotype of the correct type species, Reinholdella dreheri Brotzen, 1948 (= Discorbis dreheri Bartenstein sensu ten Dam and Reinhold, 1942). The invalid neotype of Reinholdella dreheri (Bartenstein), erected by Loeblich and Tappan (1987) (that should have been referred to as the neotype of Discorbis dreheri Bartenstein), is illustrated by scanning electron microscope (SEM) photography and redescribed. Some of the taxonomic confusion surrounding the species Discorbis dreheri Bartenstein, 1937 is illustrated from the variable morphotypes in the type material. An important species ascribed to Reinholdella, R. macfadyeni (ten Dam), is illustrated and its features compared with the type specimen. The holotype of the type species and other species illustrated have only one aperture. Species assigned to Reinholdella require re-assessment.